The Microstructure of Aluminum A5083 Butt Joint by Friction Stir Welding - M., Ishak; M. A. H. M., Jasri; M., Afendi; A., Ismail (2015)
This study presents the microstructure of the aluminum A5083 butt joint surface after it has been joined by friction stir welding (FSW) process. The FSW process is a unique welding method because it will not change the chemical properties of the welded metals. In this study, MILKO 37 milling machine was modified to run FSW process on 4 mm plate of aluminum A5083 butt joint. For the experiment, variables of travel speed and tool rotational speed based on capability of machine were used to run FSW process. The concentrated heat from the tool to the aluminum plate changes the plate form from solid to plastic state. Two aluminum plates is merged to become one plate during plastic state and return to solid when concentrated heat is gradually further away. After that, the surface and cross section of the welded aluminum were investigated with a microscope by 400 x multiplication zoom. The welding defect in the FSW aluminum was identified. Then, the result was compared to the American Welding Society (AWS) FSW standard to decide whether the plate can be accepted or rejected.